2019
DOI: 10.1038/s41467-019-08528-z
|View full text |Cite
|
Sign up to set email alerts
|

Targets of complement-fixing antibodies in protective immunity against malaria in children

Abstract: Antibodies against P. falciparum merozoites fix complement to inhibit blood-stage replication in naturally-acquired and vaccine-induced immunity; however, specific targets of these functional antibodies and their importance in protective immunity are unknown. Among malaria-exposed individuals, we show that complement-fixing antibodies to merozoites are more strongly correlated with protective immunity than antibodies that inhibit growth quantified using the current reference assay for merozoite vaccine evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(125 citation statements)
references
References 57 publications
12
112
1
Order By: Relevance
“…6,46,47,[78][79][80] In a recent development, it has been shown that antibody-mediated complement fixation on merozoites via the classical pathway and the subsequent formation of the membrane attack complex is more strongly associated with immunity against malaria than is GIA activity. 81 The absence of an appreciable GIA or IIA activity as observed in our study is, therefore, not unexpected and does not afford a qualified assessment of the potential clinical efficacy of full-length MSP1 against malaria.…”
Section: Discussioncontrasting
confidence: 54%
“…6,46,47,[78][79][80] In a recent development, it has been shown that antibody-mediated complement fixation on merozoites via the classical pathway and the subsequent formation of the membrane attack complex is more strongly associated with immunity against malaria than is GIA activity. 81 The absence of an appreciable GIA or IIA activity as observed in our study is, therefore, not unexpected and does not afford a qualified assessment of the potential clinical efficacy of full-length MSP1 against malaria.…”
Section: Discussioncontrasting
confidence: 54%
“…An invasion-blocking experiment will be required to test this possibility. It is also possible that RBP2-P1 antibodies provide clinical protection through a different mechanism, such as complement fixation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Natural host immunity is critically reliant upon the complement system to protect and eliminate infections from a number of microorganisms 71 and viruses; the classical complement initiation pathway has been demonstrated to contribute to antiviral activity and protection against West Nile virus, 72 Zika, 73 influenza, 74 vaccinia virus, 75 cytomegalovirus, 76 respiratory syncytial virus, 77 and human immunodeficiency virus 78,79 . In addition, classical complement has been implicated in host defense against the pathogenic bacteria Salmonella , 71 Gonorrhea , 80 as well as against parasites 81‐83 . However, genetic variation affecting antigen identity and character can dramatically influence the susceptibility of a virus or pathogen to classical complement neutralization or lysis, even in the instance of closely related viruses 84 .…”
Section: Role In Infectious Disease: From Elimination To Evasion To Ementioning
confidence: 99%